L’apport des sources anciennes de la Renaissance à l’étude des collections - Julie Labregère (Frontière·s)
This article presents a new reading of a handwritten letter from 1466 by Antonio Ivani da Sarzana, previously published by J.R. Spencer in 1966 and N. Thomson de Grummond in 1986. It reports the discovery of an Etruscan tomb and its funeral furniture on the lands of the Abbey of San Giusto in Volterra. Ivani’s detailed description of the reliefs adorning the tank of one of the urns makes it possible to identify a precise iconography. The journey of the deceased towards the hereafter, in the act of crossing the limit between the two worlds, is depicted as a horseman draped in a large cloak and accompanied by armed servants. Research in ancient documentation and in the corpus of Hellenistic urns of Volterra allows us to compare the description of 1466 to an urn preserved in the Volterra Guarnacci Museum (inv. 108). Its iconography, composition and material correspond perfectly to Ivani’s notes. This survey highlights the contribution of Renaissance archives to our knowledge of ancient collections and archaeological discoveries, even before inventories and museums were created.